From Pulpit to Platform: Hate Speech Toward Celebrity Preachers in the Digital Public Sphere - Maya Amalia Oesman Palapah; Riza Hernawati (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
The phenomenon of celebrity preachers reflects the transformation of religious figures in the digital era, where they function not only as spiritual teachers but also as public figures subject to moral scrutiny and controversy. This study aims to analyze the patterns and characteristics of hate speech directed toward celebrity preachers, particularly in the viral case involving one of the celebrity preacher. The research focuses on identifying themes, forms, and targets of hate speech, as well as the ethical implications of online communication in religious discourse.The study employs a mixed-method approach combining quantitative and qualitative content analysis. Data were collected from 9,689 public comments on Twitter and Instagram related to posts discussing the controversy related to one of the celebrity preacher. These comments were categorized into three analytical dimensions: thematic (religion, morality, tradition), form (direct insult, call for violence, negative stereotype), and target (personal or group). The findings reveal that approximately 22% of total comments contain hate speech, with morality emerging as the dominant theme (32.1%), followed by tradition and religion. The most common form of hate speech is direct insult (29–47%), mostly aimed at individuals rather than groups. Twitter exhibits a higher concentration of hate speech than Instagram, indicating that platform affordances influence communicative behavior. Overall, hate speech toward celebrity preachers reflects not only emotional reactions but also deeper social tensions grounded in moral judgment and cultural values, underscoring the urgent need for ethical literacy in digital religious communication.